Central venous catheter insertion profile and complications among neonates in Saudi Arabia: a cross-sectional study - Hassan Al-shehri; Ahmed Elabbasy; Haifa Abdullah Alkorbi; Ilene Padua; Abdullah Ibrahim Abuharb; Amjad Ahmad Alshedookhi (BMJ Open)
Objectives To compare complications in neonates who had umbilical venous catheter (UVC) versus peripherally inserted central catheter (PICC), percentage of non-elective removal of central catheters, and to compare complications of PICC in the upper limb compared with the lower limb.Design A prospective cross-sectional cohort study.Setting Neonatal intensive care unit (NICU) in Prince Sultan Military Medical City in Riyadh, Saudi Arabia.Participants All infants who are admitted to the unit requiring central catheter insertion were included in the study.Primary outcome measure Complications of central catheters in infants admitted to the NICU.Results A total of 415 central catheters were involved in this study (206 UVCs and 209 PICCs (85 in the lower limb, 99 in the upper limb and 25 in the head and neck). The median birth weight of the neonates was 1470 grams (1000–2215). Low birth weight was the most common reason for central catheter insertion, which accounted for 59.8%. Neonatologists were the main insertor for the majority of the cases. The median dwell days for the study sample were 11.00 (7.00–16.50) days. Complications were more common across PICC cases compared with UVC cases (p=0.001). There was non-elective removal of PICC (32.1%) compared with UVC (22.8%) (p=0.035). Phlebitis, occlusion, local infiltrate and leakage were more common in PICC compared with UVC (p<0.05). However, malposition was more commonly associated with the use of UVC (mainly to the liver) (p<0.01). Central line-associated bloodstream infection (CLABSI) rate in 1000.00 dwell days was higher in the upper limb 4.6 compared with the lower limb 2.72 but was not statistically significant (p=0.63), and there was no statistically significant difference in the proportion of other complications between the upper limb and the lower limb (p>0.05).Conclusion Close monitoring during extended dwell times is crucial. Our findings underscore the importance of raising awareness of CLABSI risk factors and adhering to best practices for central catheter maintenance. Healthcare professionals should be vigilant about the differences in complication rates between PICC and UVC, tailoring their approach accordingly.